Assignment : Pentagon : how to excel in a bureaucracy - Gerstein, Daniel M., 1958-; Smith, Perry M. (Perry McCoy) (Potomac Books, an imprint of the University of Nebraska Press, 2020)
""Assignment: Pentagon" is the essential guide for the newly assigned military person, fresh civilian, or interested outsider to the Pentagon's informal set of arrangements, networks, and functions that operate in the service and joint service world."--